Two new species of Platydoryctes Barbalho and Penteado-Dias, 2000 (Hymenoptera: Braconidae: Doryctinae) from Brazil, with an identification key for species - Castro,C. S. (2020)
Abstract Platydoryctes Barbalho and Penteado-Dias 2000 is a small genus of Neotropical parasitoid wasps (Hymenoptera: Braconidae: Doryctinae) with four described species to date. Two new species of the genus are described from Brazil, and a key to species is presented in this paper.